Risk consequence assessment of dam breach in cascade reservoirs considering risk transmission and superposition. (15th February 2023) - Wang, Te; Li, Zongkun; Ge, Wei; Zhang, Hua; Zhang, Yadong; Sun, Heqiang; Jiao, Yutie
Abstract: Compared with a single reservoir, the risk in cascade reservoirs has the transmission and superposition effect, which increases the complexity of its risk consequence assessment. In view of this problem, the direct consequence ( DC ) and potential consequence ( PC ) were defined as two parts of the dam breach risk consequence of cascade reservoirs. The upstream dam-break flood inundation line and the downstream reservoir land acquisition line were taken as the upper and lower boundaries of the assessment space, which made the risk consequence assessment more intuitive and further improved its scientificity and practicability. Subsequently, the conditional probability of downstream dam breach under the upstream dam-break flood was determined to quantify the risk transmission and superposition. On this basis, the relevant concepts and formulas for calculating the dam breach risk consequence in cascade reservoirs were proposed. Taking five cascade reservoirs as examples, the risk consequences of each cascade dam breach were evaluated. The results show that the proposed method is effective in assessing the risk consequence of dam breach in cascade reservoirs and is more in line with the connotation of dam risk management, which can provide reference for the design and risk control of cascade reservoirs. Highlights: The dam breach risk consequence of cascade reservoirs is analyzed and decomposed. The assessment space of dam breach risk consequence is delimited. Conditional probabilities are used to reflect the uncertainty of risk consequence. The formulas for calculating the risk consequence of cascade dams are proposed.